2015
DOI: 10.5194/bg-12-2431-2015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of greenhouse gases (CO<sub>2</sub>, CH<sub>4</sub>, N<sub>2</sub>O) along the Zambezi River and major tributaries, and their importance in the riverine carbon budget

Abstract: Abstract. Spanning over 3000 km in length and with a catchment of approximately 1.4 million km2, the Zambezi River is the fourth largest river in Africa and the largest flowing into the Indian Ocean from the African continent. We present data on greenhouse gas (GHG: carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O)) concentrations and fluxes, as well as data that allow for characterization of sources and dynamics of carbon pools collected along the Zambezi River, reservoirs and several of its tribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
98
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 65 publications
12
98
1
2
Order By: Relevance
“…Another possible explanation is methane oxidation, which was shown to remove large fractions of CH 4 in some estuaries (de Angelis and Scranton, 1993;Abril et al, 2007). Although CH 4 concentrations tended to be higher during the wet season, a clear seasonal pattern of CH 4 concentrations was not apparent, which is in line with observations at other tropical Teodoru et al, 2014) and subtropical (Musenze et al, 2014) sites.…”
Section: Chsupporting
confidence: 69%
See 1 more Smart Citation
“…Another possible explanation is methane oxidation, which was shown to remove large fractions of CH 4 in some estuaries (de Angelis and Scranton, 1993;Abril et al, 2007). Although CH 4 concentrations tended to be higher during the wet season, a clear seasonal pattern of CH 4 concentrations was not apparent, which is in line with observations at other tropical Teodoru et al, 2014) and subtropical (Musenze et al, 2014) sites.…”
Section: Chsupporting
confidence: 69%
“…The generally positive relationship between CH 4 and pCO 2 has been observed in other tropical aquatic systems (Teodoru et al, 2014;Borges et al, 2015) and is indicative of organic matter decomposition as a source of both gases. The strong response of CH 4 to tidal variations indicates that CH 4 is produced in the sediments and released when the hydrostatic pressure drops during falling tide.…”
Section: Chsupporting
confidence: 53%
“…Finally, in order to further characterize human-impacted river networks compared to relatively pristine ones, and also to compare temperate and tropical rivers we compared CH 4 and N 2 O in the Meuse with our own data-sets obtained in the Congo and Zambezi rivers (Borges et al, 2015a;Teodoru et al, 2015) (Fig. 12).…”
Section: Tablementioning
confidence: 99%
“…Enhanced nutrient inputs will fuel primary production leading to low CO 2 and high CH 4 concentrations, the latter related to enhanced organic matter delivery to sediments . Other human impacts that affect carbon and nitrogen cycling in river networks that can potentially influence cycling of GHGs are river bank stabilization and floodplain drainage that disrupt the river-wetland connectivity that is important for CO 2 and CH 4 dynamics in rivers (Abril et al, 2014;Teodoru et al, 2015;Borges et al, 2015aBorges et al, , 2015bSieczko et al, 2016). The introduction of invasive animal species such as the zebra mussel (Dreissena polymorpha) in US rivers and lakes (Caraco et al, 1997;Evans et al, 2011) (Hussner, 2012), some with high production and biomass (Hussner, 2009); invasive floating macrophytes such as the water hyacinth (Eichhornia crassipes) have been documented to increase CO 2 and CH 4 levels in tropical rivers (Koné et al, 2009(Koné et al, , 2010, but this remains undocumented in temperate rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Degassing downstream the turbines is a wellknown phenomenon linked to pressure change and turbulence once the water has been released (Galy-Lacaux et al, 1997). Though it is not a new pathway, downstream degassing has been neglected in the past decade, even if few studies pointed out (Abril et al, 2005;Kemenes et al, 2007;Maeck et al, 2014;Teodoru et al, 2015) that it could be a significant one. Results from the Petit Saut reservoir study in French Guiana (Abril et al, 2005) have shown that degassing and emissions from the river downstream of the dam, if not the main pathway during the two first years after impoundment, becomes heavily dominant when accounted over the span of the first ten years after impoundment.…”
Section: Introductionmentioning
confidence: 99%